Localization ofMHC class I and II genes in zebu and crossbred cattle - KARTHICKEYAN, S M K; RAI, AMIT KUMAR; GTIRUMURUGAAN, K; KANAKARAJ, P (The Indian Journal of Animal Sciences, 2011)
Two probes, pBoLA (bovine lymphocyte antigen; class I) and DRA (class II) were localized to Bos indicus chromosome 23 between bands 15 and 22 (23q15-22) and further confirmed the close linkage of MHC genes (class I and class II). Tyramide signal amplification was carried out to localize the genes in the small acrocentric chromosome for better visualization and photography in an epifluorescent microscope without any special device fitted for software analysis and signal magnification. The gene localization in Bos indicus cattle is identical to the localization of this gene in Bos taurus cattle. Â